The Effect of Giving Salam Leaf Water Decoction on Reducing Uric Acid Levels in the Elderly in the UPT Batu Aji Work Area, Batam City, 2021 - Elisabeth Nona Yunita; Siska Natalia; Rizki Sari Utami (Journal of Health Sciences, Medicine, Biotechnology, and Pharmaceutical Research, 2025)
The prevalence of gout in Indonesia is the fourth largest country in the world whose population suffers from gout. 35% of gout occurs in men over the age of 45 years. Joint disease in those aged 55-64 years is 45%. Age 65-74 years 51.9%. Age ≥ 75 years 54.8%. The incidence of joint disease based on diagnosis by health workers in Indonesia is 7.3 and based on diagnosis or symptoms 24.7% (RISKESDAS, 2018). This type of research is quantitative using a quasi-experimental research method with pre-test and post-test with control methods. The population of all elderly people suffering from gout who underwent examination and treatment in the Batu Aji Health Center UPT area, namely 140 people as of April 2021. The number of samples in this study was 30 people, divided into 15 elderly people in the experimental group and 15 elderly people in the experimental group. Control. Based on the results of research and data processing that has been carried out by researchers, regarding the effect of boiling bay leaf water on reducing uric acid levels in the elderly in the Batu Aji Health Center UPT area, Batam City in 2021 with a total of 30 respondents, consisting of 15 intervention groups and 15 control groups . The research carried out not only provides conclusions but also provides suggestions to various parties to help improve health and prevent complications in gout patients.